The effects of early experiences at home and pre-school on gains in English and mathematics in primary school: a multilevel study in England - Sylva, K; Sammons, P; Chan, L; Melhuish, E; Siraj-Blatchford, I; Taggart, B (2013)
Few studies have explored whether learning experiences during the pre-school period differentiate rates of growth in academic skills during primary school. Here, findings are presented from a longitudinal study on a representative sample of 2,800 children in the UK. This study examined the contribution of the early years Home Learning Environment (HLE) and pre-school quality to children's academic progress between ages 7 and 11 (i.e. years 2 and 6 of primary school) in English and mathematics. Results indicate that a rich early HLE leads to accelerated progress in English and mathematics between 7 and 11 years. Quality rather than mere attendance was the pre-school factor which promoted academic progress. Children who had a stronger 'profile' at school accelerated away from other children over the primary period. The benefits of high quality home and pre-school environments appear to be long-lasting and cumulative, improving children's developmental trajectories by enabling them to make greater learning gains compared to their peers who experienced lower pre-school quality. © 2013 Springer Fachmedien Wiesbaden.